IMPLEMENTASI JARINGAN LAN TESTING SEBAGAI DASAR PEMAHAMAN INTERNET - Fauzi Aditia Putra; Muhamad Fajar; Ariansa Dos Santos; Darrent Rhafa Raditia Adu; Duga Saka Uni; Melania Ellen Tjitrodjojo; Muhamad Dafa Wildan; Ridha Adwiyai Syauqi Hilmi; Yuda Wahyu Saputro (Abdi Jurnal Publikasi, 2026)
The development of information and communication technology has transformed educational processes and digital interaction in society. Computer networking knowledge, particularly Local Area Network (LAN), is an important foundation for understanding internet infrastructure. However, junior high school students often have limited technical knowledge regarding network systems. This community service activity aimed to introduce basic computer networking concepts through LAN testing implementation at SMPI Hidayatul Athfal. The methods used included theoretical explanation, practical cable making, LAN simulation, and network connectivity testing. Evaluation was carried out through observation and learning assessment. The results showed improved student understanding regarding network components, internet connectivity, and practical networking skills. This activity contributes to improving digital literacy and supports schools in implementing practical technology-based learning.